Efektivitas Penambahan Sludge Zone Pada Sequencing Batch Reactor untuk Mengolah Limbah Cair Rumah Makan - Hendrasarie, Novirina; Raden Kokoh H.; Firra R.; Yayok SP; Ranno MR. (Journal of Research and Technology, 2022)
A Sequencing Batch Reactor is a wastewater treatment plant that degrades pollutants in wastewater using microbes.. The purpose of this research is to improve the performance of a Sequencing Batch Reactor (SBR) by incorporating a sludge zone. The addition of a sludge zone in the Sequencing Batch Reactor (SBR) allows the sludge formed as a byproduct of processing waste water to be accommodated rather than eroded back into the fluid. The method employed compares SBR with and without the addition of a sludge zone. Furthermore, the hydraulic retention time (12, 24, 36, and 48 hours) and air flowrate (7 and 14 ml/minute) were investigated. According to the study's findings, the SBR with the addition of the sludge zone removed 97% COD, 79% total N, 53% total P, 85.6% TSS, and 81% fatty oil. Meanwhile, SBR without a sludge zone yielded 96% COD, 72% total N, 45% total P, 82% TSS, and 74% oil and grease.